Analisis Pemungutan Pajak Daerah di Kabupaten Bolaang Mongondow - Mokodompit, Samsul; Nangoi, Grace B; Ilat, Ventje (Universitas Sam Ratulangi, 2017)
Abstract. Local tax is a compulsory contribution to an area owed by an individual or a coercive body under the Act by not obtaining direct remuneration and being used for regional purposes for the greatest possible prosperity of the people. Collection is a series of activities ranging from the collection of data objects and tax subjects, determination of the amount of tax payable until tax collection activities to the taxpayer and supervision of its payment. The purpose of this study is to analyze the implementation of local tax collection in Bolaang Mongondow regency and analyze the obstacles and efforts undertaken. This research uses qualitative method with exploratory approach. Local Government Finance Agency of Bolaang Mongondow is the object of this research. Data were obtained by in-depth interviews and documentation study. Key informants were determined purposively to obtain the accurate information. Semi structured in-depth interviews were conducted to collect data. Validity or credibility of the data was gained by triangulation. Data were analysed by using Miles and Huberman model which consists of data reduction, display data and drawing conclusion. The results show that the implementation of local tax collection is in accordance with Government Regulation No. 55 of 2016 consists of 1) types of taxes and tax setting arrangements in local regulations 2) taxpayer registration and tax period 3) determination, payment and tax reporting 4) billing and write-off of tax receivables 5) objections and appeals. While the constraints encountered in the collection process consist of human resources, budget and facilities and awareness of taxpayers. Efforts made are in the form to improve the human resources, the budget and facilitation, leadership and socializationKeywords: Local Tax Collection, Human Resources, Budget and Facilities, Awareness of Taxpayer.Abstrak. Pajak daerah adalah kontribusi wajib kepada daerah yang terutang oleh orang pribadi atau badan yang bersifat memaksa berdasarkan Undang-Undang dengan tidak mendapatkan imbalan secara langsung dan digunakan untuk keperluan daerah bagi sebesar-besarnya kemakmuran rakyat. Pemungutan adalah suatu rangkaian kegiatan mulai dari penghimpunan data objek dan subjek pajak, penentuan besarnya pajak yang terutang sampai kegiatan penagihan pajak kepada wajib pajak serta pengawasan penyetorannya. Tujuan penelitian ini untuk menganalisis pelaksanaan pemungutan pajak daerah di Kabupaten BolaangMongondow, kendala yang menjadi penghambat dan upaya-upaya yang dilakukan. Penelitian ini menggunakan metode kualitatif dengan pendekatan eksploratori. Pemerintah Kabupaten Bolaang Mongondow Badan Keuangan Daerah sebagai objek penelitian. Data diperoleh melalui teknik wawancara mendalam dan studi dokumentasi. Informan kunci ditentukan secara purposive untuk mendapatkan hasil informasi yang tepat dan akurat. Wawancara menggunakan In-depth interview semi terstruktur. Metode triangulasi sumber digunakan dalam pengujian validitas atau kredibilitas data. Teknik analisis yang digunakan yaitu model Miles and Huberman yang terdiri dari data reduction, data display dan drawing conclusion. Hasil penelitian menunjukkan bahwa pelaksanaan pemungutan pajak daerah sudah sesuai dengan PP No 55 Tahun 2016 yang terdiri dari 1) jenis-jenis pajak dan pengaturan penetapan pajak dalam peraturan daerah; 2) pendaftaran wajib pajak dan masa pajak; 3) penetapan, pembayaran dan pelaporan pajak; 4) penagihan dan penghapusan piutang pajak; 5) keberatan dan banding. Kendala yang ditemui dalam proses pemungutan terdiri dari sumber daya manusia, anggaran dan fasilitas serta kesadaran wajib pajak. Upaya yang dilakukan yaitu dalam bentuk perbaikan sumber daya manusia, anggaran dan fasilitis, kepemimpinan dan sosialisasi.Kata Kunci : Pemungutan Pajak Daerah, Sumber Daya Manusia, Anggaran dan Fasilitas, Kesadaran Wajib Pajak.